Education and Training Regimes within the Swiss Vocational Education and Training System. A Comparison of the Cantons of Geneva, Ticino, and Zurich in the Context of Educational Expansion - Philipp Gonon; Lena Freidorfer-Kabashi (MDPI AG, 2021)
Swiss Vocational Education and Training (VET) is based on national legislation which was introduced in the 1930s and renewed in the 1960s (as well as in the 1970s and in 2002). At first, the goal of the national VET legislation was to further Vocational Education and Training in order to support small and medium enterprises; however, later, it also included industry and services and has more recently grown to support the learners themselves. The 1963 national legislation and the following implementation acts in the cantons were decisive in shaping the Swiss VET system from a historical and comparative perspective. We argue that still today we do not have a unified, national system of education, but rather e cantonal modes of education and also of VET. However, the cantonal actors-with a specific focus on Ticino, Geneva, and Zurich-argue with similar justifications, when it comes to the reform of VET. Nevertheless, within this national legal framework, the cantons adopt rather different solutions. The result is that different (language specific) regional pathways of VET were established, based on various education and training regimes. In this research paper, we aim to concentrate on the years from 1950 to 1970, a period that turns out to be particularly significant for the development of Swiss VET. We focus our research on the introduction of the Vocational Training Act in 1963 and look in detail at the extent to which the cantons developed their corresponding implementation acts from the perspectives of different motives and logics.